4
$\begingroup$

Solve the ODE $$ \frac{\partial^{2} u }{\partial \eta^{2}} + \frac{\eta}{2\nu} \frac{\partial}{\partial\eta} = 0 $$

The book uses integrating factor = $ e^{\int\frac{\eta}{2\nu} d\eta}$

Can someone explain from here, how to proceed?

I get $ IF = e^\frac{\eta^{2}}{4\nu}$. Multiply this with the ODE. Not sure what to do next? Because the answer the book gives is $$ \frac{\partial u}{\partial \eta} = A e^{\frac{-\eta^{2}}{4/nu}}$$ and I don't understand how to get this.

$\endgroup$
  • 1
    $\begingroup$ The idea of IF is that after multiplication you will get something of the form $fg'+f'g = (fg)'$. $\endgroup$ – user147263 Jan 24 '16 at 1:40
  • $\begingroup$ \begin{align} u'' + \frac{n}{2\nu}u' &= 0 \\ \implies \bigg[ u' \exp \bigg( \frac{n^{2}}{4\nu} \bigg) \bigg]' &= 0 \\ \implies u' \exp \bigg( \frac{n^{2}}{4\nu} \bigg) &= A \\ \implies u' &= A \exp \bigg( \frac{-n^{2}}{4\nu} \bigg) \end{align} $\endgroup$ – Mattos Jan 24 '16 at 3:57
1
$\begingroup$

$$u''(\eta)+\frac{u'(\eta)\eta}{2\nu}=0\Longleftrightarrow$$


Let $u'(\eta)=w(\eta)$, which gives $u''(\eta)=w'(\eta)$:


$$w'(\eta)=-\frac{\eta w(\eta)}{2\nu}\Longleftrightarrow$$ $$\frac{2vw'(\eta)}{w(\eta)}=-\eta\Longleftrightarrow$$ $$\int\frac{2\nu w'(\eta)}{w(\eta)}\space\text{d}\eta=\int-\eta\space\text{d}\eta\Longleftrightarrow$$ $$2\nu\ln(w(\eta))=-\frac{\eta^2}{2}+\text{C}\Longleftrightarrow$$ $$w(\eta)=e^{-\frac{\eta^2-2\text{C}}{4\nu}}\Longleftrightarrow$$ $$w(\eta)=e^{-\frac{\eta^2+\text{C}}{4\nu}}\Longleftrightarrow$$ $$u'(\eta)=e^{-\frac{\eta^2+\text{C}}{4\nu}}\Longleftrightarrow$$ $$u(\eta)=\int e^{-\frac{\eta^2+\text{C}}{4\nu}}\space\text{d}\eta$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.